A descriptive and model-based spatial comparison of the standardised mortality ratio and the age-standardised mortality rate - Sibylle Sturtz; Katja Ickstadt (Geospatial Health, 2007)
The number of deaths in a particular connection can be expressed in different ways. In spatial epidemiology, two widely used measures are the standardised mortality ratio (SMR) and the so called mortality rate. This paper compares these two ways of expressing mortality using a descriptive and a model-based approach. Age-standardised versions of both terms have been investigated by a descriptive analysis of temporal and spatial patterns and by employing different Bayesian spatial models to study their performance. We observed that the SMR and the age-standardised mortality rate (ASM) are strongly correlated and lead to comparable results. This demonstration is based on mortality data by age, stratified into five-year ranges, from the cause-of-death-statistics with reference to ischaemic heart disease and lung cancer in 54 counties of the German state of North Rhine Westphalia between 1980 and 1997.